Contouring the Mandible for Aesthetic Enhancement in Asian Patients - Lee, Tae Sung; Park, Sanghoon (Facial Plastic Surgery, 2020)
A prominent mandible that gives a squared face in Asians is considered unattractive as it imparts a coarse and masculine image. Mandibular contouring surgery allows slender oval faces. The purpose of conventional mandible reduction is to make the lower face appear slim in frontal view and to have a smooth contour in lateral view. As shaping the lateral contour of the mandible alone may result in minimal improvement in the frontal view, surgical techniques to reduce the width of the lower face through narrowing genioplasty (i.e., the “V-line” surgery) and sagittal resection of the lateral cortex should be combined. Examination of the shape and symmetry, the relationship between the maxilla and the mandible, understanding overlying soft tissue contribution, and understanding the overall balance of the face are mandatory. An important factor influencing ideal facial shape is patient's personal preference, which is often influenced by his/her ethnic and cultural background. Especially when consulting patients of different nationalities or ethnic backgrounds, careful attention should be paid to the patient's aesthetic sensibility regarding the ideal or desirable facial shape. Narrowing the chin and modification of chin shape can be accomplished by narrowing genioplasty with central strip resection. This midsymphyseal sectioning procedure yields safe and very satisfactory results. This procedure not only augments the narrowing effect by leaving soft tissues attached to the bone but also enables modification of chin shape by altering the shape of resection. The surgeon should customize the surgery based on a comprehensive assessment of the patient's preoperative chin and mandible morphology complemented by an assessment of their aesthetic goals.
Keywords: facial bone contouring; mandible reduction; lower face contouring; V-line surgery